Recurring oral erythema multiforme-like lesions elicited by COVID-19 infection: a case report - Al-Ak’hali, Mohammed Sultan; Esam Halboub; Wael Ibraheem; Hamza Khalid Khan; Hummadi, Abdulkreem Mohammed (Brazilian Dental Science, 2022)
Oral mucosa could be the first site infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) –the causative agent of coronavirus disease 2019 (COVID-19). Indeed, different oral and paraoral lesions, conditions and symptoms have been reported in patients with COVID-19. Experts thought that such oral lesions could be secondary to the COVID-19-associated deterioration of systemic health or due to treatments of COVID-19. We present here a case of a 24-year-old male presented with painful multiple ulcers involving the labial and buccal mucosae bilaterally after a while of feeling very mild symptoms that laboratory-confirmed by reverse-transcription polymerase chain reaction to be COVID-19. Involvement of eyes was also reported. The above clinical presentation was consistent with minor erythema multiform. Many topical preparations were prescribed but with limited improvement. Hence, oral prednisolone was prescribed with a 40-mg loading dose that was tapered by 10 mg every 3 days. Complete healing of oral mucosa was observed on the 10 day. Strikingly, the patient got affected with the second episode of similar oral lesions 5 months later without any apparent triggering factors, suggestive a long term effects of COVID-19 in a subset of patients. The present case report provides dentists with useful information and increases their awareness regarding possible involvement of oral cavity with multiple ulcerative lesions associated with COVID-19. KEYWORDS Oral erythema multiforme; Oral manifestations; COVID-19; Case report.